2002
DOI: 10.1016/s0168-9002(02)00890-2
|View full text |Cite
|
Sign up to set email alerts
|

Rayleigh scattering in rare-gas liquids

Abstract: The Rayleigh scattering length has been calculated for rare-gas liquids in the ultraviolet for the frequencies at which they luminesce. The calculations are based on the measured dielectric constants in the UV in the gas phase, in some cases extrapolated to the wavelength of luminescence. The scattering length may place constraints on the design of some largescale detectors, using UV luminescence, being proposed to observe solar neutrinos and dark matter. Rayleigh scattering in mixtures of rare-gas liquids is … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
75
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(82 citation statements)
references
References 34 publications
(27 reference statements)
7
75
0
Order By: Relevance
“…The results of calculations of scattering coefficients are given in Table I. We found that our results for scattering lengths and dielectric constants, ǫ He = 1.086 ± 0.006 and ǫ N e = 1.5 ± 0.2, are in agreement with those obtained by Seidel et al [5] using extrapolation of experimental refraction indices: ǫ He = 1.077, ǫ N e = 1.52, R He = 600 cm , and R N e = 60 cm. Our calculations has been done to check the previous results and to evaluate the uncertainty.…”
Section: Figsupporting
confidence: 89%
See 1 more Smart Citation
“…The results of calculations of scattering coefficients are given in Table I. We found that our results for scattering lengths and dielectric constants, ǫ He = 1.086 ± 0.006 and ǫ N e = 1.5 ± 0.2, are in agreement with those obtained by Seidel et al [5] using extrapolation of experimental refraction indices: ǫ He = 1.077, ǫ N e = 1.52, R He = 600 cm , and R N e = 60 cm. Our calculations has been done to check the previous results and to evaluate the uncertainty.…”
Section: Figsupporting
confidence: 89%
“…[5]. The compressibility κ T of He and Ne are 208×10 −10 and 4.95×10 −10 cm 2 /dyne; ρ is the density.…”
Section: Figmentioning
confidence: 98%
“…Table I shows the optical model parameters used in LUXSIM optimized for replication of the experimental data. The indices of refraction of xenon and quartz were based on previous data [49,50], while the Rayleigh scattering length came from a theoretical calculation [51]. Of these, the parameters with the most impact were found to be the reflectivity of the PTFE walls in the liquid and the photon absorption length in the liquid.…”
Section: B Optical Modelmentioning
confidence: 99%
“…Both absorption due to optical transitions starting from the van der Waals minimum of the lower potential curve in the region of the so-called first excimer continuum and scattering due to increasing fluctuations of the index of refraction when approaching the resonance lines from longer wavelengths have been identified in that reference as the reason for light attenuation extending far out into the red wings of the resonance lines. Rayleigh scattering in rare gas liquids has also more recently been discussed in [16] resulting in a scattering length of 90 cm. Here we assume that the processes discussed in these publications are also relevant for the attenuation in liquid argon for wavelengths close to the resonance lines of argon at 104.82 nm 106.67 nm [17], and longer wavelengths.…”
Section: Introductionmentioning
confidence: 99%